2003
DOI: 10.1073/pnas.1735462100
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal near infrared oximetry of hypoxic stress in fetal sheep brain in utero

Abstract: The feasibility of transabdominal near-infrared (NIR) spectroscopy for detecting and quantifying fetal hypoxia in utero is demonstrated in a pregnant ewe model. A frequency domain NIR spectroscopy probe, consisting of two detectors and six sources operating at three wavelengths (675, 786, and 830 nm), was placed on the maternal abdomen directly above the fetal head. Fetal hypoxia was indirectly induced through occlusion of uterine blood flow for Ϸ3 min. NIR photon diffusion measurements were made during a base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 43 publications
0
27
0
1
Order By: Relevance
“…Reflectance diffuse spectroscopy measurement of tissue oxygenation is a well-established methodology (21,32,34,(41)(42)(43)(44). In addition, validation of our diffuse optical reflectance approach in tissues has been reported in brain activation (33,45) and tumor studies (46).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Reflectance diffuse spectroscopy measurement of tissue oxygenation is a well-established methodology (21,32,34,(41)(42)(43)(44). In addition, validation of our diffuse optical reflectance approach in tissues has been reported in brain activation (33,45) and tumor studies (46).…”
Section: Resultsmentioning
confidence: 88%
“…Reflectance diffuse spectroscopy is a well-documented technique of measuring tissue optical properties, including concentrations of oxyhemoglobin and deoxyhemoglobin (21,32,34,35,(41)(42)(43)(44). From these quantities tissue hemoglobin oxygen saturation, or SO 2 , can be calculated.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of absolute measurements for in vivo interrogation of cerebrovascular health has been shown in animal models [35], [40], [41], [42]. Briefly, Saxena et al .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Choe et al . demonstrated that absolute values of [HbO 2 ] and [Hb] can be used to measure hypoxic stress in fetal sheep brain in utero and emphasized the potential implications of such measurements for the imaging of the human fetus [41]. Such diagnostic and/or long-term monitoring approaches presented above could only be made possible by quantification of concentration and saturation of hemoglobin in absolute terms.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, an optical fetal heart rate detection (OFHR) system has been designed and developed using low-cost, low-power IR light (890 nm with optical power < 68 mW) and a commercially available silicon photo-detector ). Previous literature Chance 2005;Zourabian et al 2000;Nioka et al 2005;Vintzileos et al 2005;Choe et al 2003) shows that the Source-Detector separations depends on the type of sources and the photo-detectors implemented in their studies. Since in our work the developed instrument utilizes low optical power, the source-to-detector separation plays an important role as it affects the detectivity of the photo-detector.…”
Section: Adaptive Filtering Applications 142mentioning
confidence: 99%